Electrophysiological and Morphological Features of Rebound Depolarization Characterized Interneurons in Rat Superficial Spinal Dorsal Horn - Zhu, Mengye; Yan, Yi; Cao, Xuezhong; Zeng, Fei; Xu, Gang; Shen, Wei; Li, Fan; Luo, Lingyun; Wang, Zhijian; Zhang, Yong; Zhang, Xuexue; Zhang, Daying; et al. (Frontiers in Cellular Neuroscience, 2021)
Substantia gelatinosa (SG) neurons, which are located in the spinal dorsal horn (lamina Ⅱ), have been identified as the ‘central gate’ for the transmission and modulation of nociceptive information. Rebound depolarization (RD), a biophysical property mediated by membrane hyperpolarization that is frequently recorded in the central nervous system, contributes to shaping neuronal intrinsic excitability and, in turn, contributes to neuronal output and network function. However, the electrophysiological and morphological properties of SG neurons exhibiting RD remain unclarified. In this study, whole-cell patch-clamp recordings were performed on SG neurons from parasagittal spinal cord slices. RD was detected in 44.44% (84 out of 189) of the SG neurons recorded. We found that RD-expressing neurons had more depolarized resting membrane potentials, more hyperpolarized action potential (AP) thresholds, higher AP amplitudes, shorter AP durations and higher spike frequencies in response to depolarizing current injection than neurons without RD. Based on their firing patterns and morphological characteristics, we propose that most of the SG neurons with RD mainly displayed tonic firing (69.05%) and corresponded to islet cell morphology (58.82%). Meanwhile, subthreshold currents, including the hyperpolarization-activated cation current (Ih) and T-type calcium current (IT), were identified in SG neurons with RD. Blockage of Ih delayed the onset of the first spike in RD, while abolishment of IT significantly blunted the amplitude of RD. Regarding synaptic inputs, SG neurons with RD showed lower frequencies in both spontaneous and miniature excitatory synaptic currents. Furthermore, RD-expressing neurons received either Aδ- or C-afferent-mediated monosynaptic and polysynaptic inputs. However, RD-lacking neurons received afferents from monosynaptic and polysynaptic Aδ fibers and predominantly polysynaptic C-fibers. These findings demonstrate that SG neurons with RD have a specific cell-type distribution, and may differentially process somatosensory information compared to those without RD.